Shielding and activation of a viral membrane fusion protein - Steinar Halldorsson (Nature Communications, 2018)
Viral fusion proteins undergo extensive conformational changes during entry but intermediate conformations often remain unknown. Here, the authors show how Gn of Rift Valley fever virus fusion protein shields hydrophobic fusion loops of Gc and how these loops embed in the target membrane at acidic conditions.